REDUCTION OF TOTAL ORGANIC CARBON AND CORRELATION WITHIN ABUNDANCE AND DIVERSITY OF PHYTOPLANKTON IN AQUAPONICS SYSTEM - Indah Pratiwi Juliana SY; Rara Diantari; Eko Efendi (AQUASAINS, 2015)
Water quality plays an important role in aquaponics system. Water chemistry parameter that may affect water quality is total organic carbon. Sources of carbon in the aquaponics system mainly derived from the decomposition of organic matter which derived from artificial feed and plant respiration. The research was conducted to study the reduction of total organic carbon concentration in the aquaponic system and the relation of abundance and diversity of phytoplankton. This research using different amount of ipomoea (Ipomoea aquatica) consist of 10, 20, and 30 rods and control treatments which use without ipomoea. The results showed that all of ipomoea treatments can reduce the amount of total organic carbon concentration in the aquaponics system. This research showed that nutrients cycle in the aquaponics system, especially total organic carbon dissolved in water is influenced by many factors such as plants, fish and primary productivity which determined by the plankton. Furthermore, a positive correlation occurred between total organic carbon concentration of the abundance and diversity of phytoplanktons (r = 0.5925; r = 0.6364). These results can be used for preliminary study of nutrient cycle model in aquaponic system.